Efektivitas Terapi Infrared Untuk Pengurangan Nyeri Pada Pasien Cephalgia - Mochamad Nursa'id; Wiek Israwan; Amin Zakaria; Fransisca Xaveria Hargiani (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: to identify the effect of infra red on the reduction of pain in cephalgia.Methods: This studyused a pre experimental method with one group pre-post test design. This study conducted in RSUD Pasirian, Lumajang. 30 patients with cephalgia with age 34-75 years old.Study participant received twice a weektreatment sessions of of infra red. Outcome measures were a score of VASResults: 30 patients were 22 women and 8 men at the end of the treatment showed reducing pain in cephalgia. Normality test with Shapiro-wilk test, the data obtained from the treatment group are abnormal distributed. The test result with Wilcoxon obtainedP value = 0.000. If P < 0.005 then the hypothesis test is that H0 is rejected and H1 is accepted, this shows that there is a difference before and after treatment, so there is a difference between the pre-test and post-test.Conclusion: it can be concluded that the infra red given has an effect of reducing pain in cephalgia. A total of 29 respondents from 30 respondents or about 96.6% of patients with a medical diagnosis of cephalgia were proven to have an effect, namely a reduction in pain on the VAS scale after being given infrared.